DIAGNOSTIC AND MANAGEMENT APPROACH ON ACUTE INTOXICATION PATIENTS IN EMERGENCY SETTING: A CASE REPORT - Elfi Rahmi (Faculty of Medicine Universitas Kristen Duta Wacana, 2019)
Background: Acute intoxication is one common cause of loss of consciousness in emergency setting. However, its diagnosis and management usually neglected. In addition, multiple toxin might make etiological diagnosis and management more difficult. Aim: This report describes the approach to diagnose and manage acutely intoxicated patients with suspected multiple substance in emergency unit of Dr. Sardjito Hospital Case description: A 30-year-old male was admitted to emergency unit with loss of consciousness and return of spontaneous circulation after resuscitation prior to admission. He was comatose, with miosis and decreased physiological reflex. Further laboratory examination discovered decreased renal function and high level of serum alcohol. The patient regained his consciousness after he was given naloxone, dexamethasone, mecobalamin, and pantoprazole. Conclusion: In the future, there is a need to integrate substance intoxication management to the algorithm of loss of consciousness management to improve the quality of acute intoxication management.